2019
DOI: 10.3390/nu11112612
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Green Tea Consumption on Colorectal Cancer Varies by Lifestyle Factors

Abstract: The inconsistent findings regarding green tea intake and colorectal cancer (CRC) risk in several epidemiological studies might result from variations in lifestyle factors. Therefore, we examined whether increased green tea intake was associated with a decreased risk of CRC and how the risk of CRC was altered by the protective effect of green tea consumption and five health-related factors. A case-control study including 2742 participants (922 cases and 1820 controls) was conducted in Korea. Green tea consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…A meta-analysis revealed a nonlinear inverse relationship between fruit and vegetable consumption and CRC [ 53 ]. Following the present results, previous studies have demonstrated an inverse to no association when examining whole grains, fibre, polyphenols, dietary vitamin D, calcium, and dairy products [ 32 , 33 , 35 , 54 - 58 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A meta-analysis revealed a nonlinear inverse relationship between fruit and vegetable consumption and CRC [ 53 ]. Following the present results, previous studies have demonstrated an inverse to no association when examining whole grains, fibre, polyphenols, dietary vitamin D, calcium, and dairy products [ 32 , 33 , 35 , 54 - 58 ].…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that dietary vitamin D, calcium-rich dairy products, whole grains, and fibre were shown to be protective against CRC risk [ 31 - 34 ]. A case-control study conducted in Korea reported an association between green tea intake and the risk of CRC [ 35 ]. According to this study, moderate green tea intake elevated the risk of CRC; however, the risk was reduced when a higher amount of green tea was consumed [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that it is unlikely that green tea itself increases blood LPS concentration. Meanwhile, epidemiological studies have reported that people with a dietary habit of consuming both green tea and alcohol have an increased risk of esophageal cancer [ 74 ] and colorectal cancer [ 75 ]. In other words, the ingestion of green tea and alcohol may damage the epithelium of the gastrointestinal tract, which may reduce the intestinal barrier function and promote LPS influx.…”
Section: Discussionmentioning
confidence: 99%
“…A previous case-control study of colorectal cancer risk with coffee [ 10 ] and green tea [ 28 ] consumption in Korea showed that high coffee and green tea consumption may be associated with a lower risk of colorectal cancer. To the best of our knowledge, there are no large-scale population-based studies that have investigated the association between coffee and green tea consumption and the risk of colorectal cancer considering lifestyle factors in the Korean population.…”
Section: Introductionmentioning
confidence: 99%